2019
DOI: 10.3389/fgene.2019.00185
|View full text |Cite|
|
Sign up to set email alerts
|

Myometrial Transcriptional Signatures of Human Parturition

Abstract: The process of parturition involves the transformation of the quiescent myometrium (uterine smooth muscle) to the highly contractile laboring state. This is thought to be driven by changes in gene expression in myometrial cells. Despite the existence of multiple myometrial gene expression studies, the transcriptional programs that initiate labor are not known. Here, we integrated three transcriptome datasets, one novel (NCBI Gene Expression Ominibus: GSE80172) and two existing, to characterize the gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 52 publications
5
45
0
Order By: Relevance
“…Notably, myometrial ZEB1 and PLCL1 mRNA levels both decrease from the term nonlabor to the term labor state, which contrasts with our observations that these two genes exhibit an increase of expression from the NP to the term TP state (Figure ). At the genome‐wide level, 60 of 126 genes that have significant changes of mRNA levels between the term nonlabor and the term labor state either show no change (55 genes) or in an opposite direction (5 genes) of expression in our studies . While this discrepancy could result from data variances of different cohorts of human subjects, it is also possible that these 60 genes could be under tight regulation at the NP, the term nonlabor and the term labor states for potential stage‐specific functions.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Notably, myometrial ZEB1 and PLCL1 mRNA levels both decrease from the term nonlabor to the term labor state, which contrasts with our observations that these two genes exhibit an increase of expression from the NP to the term TP state (Figure ). At the genome‐wide level, 60 of 126 genes that have significant changes of mRNA levels between the term nonlabor and the term labor state either show no change (55 genes) or in an opposite direction (5 genes) of expression in our studies . While this discrepancy could result from data variances of different cohorts of human subjects, it is also possible that these 60 genes could be under tight regulation at the NP, the term nonlabor and the term labor states for potential stage‐specific functions.…”
Section: Discussionmentioning
confidence: 61%
“…At the genome-wide level, 60 of 126 genes that have significant changes of mRNA levels between the term nonlabor and the term labor state either show no change (55 genes) or in an opposite direction (5 genes) of expression in our studies. 75 While this discrepancy could result from data variances of different cohorts of human subjects, it is also possible that these 60 genes could be under tight regulation at the NP, the term nonlabor and the term labor states for potential stagespecific functions. These observations justify future examinations on the timely change of myometrial transcriptome at multiple states for a high-resolution view of gene expression dynamics.…”
Section: Novelty Of the Studymentioning
confidence: 99%
“…Understanding human parturition is essential to tackle the challenge of prematurity, which affects 15 million neonates every year 46 . Bulk transcriptomic studies of the cervix 711 , myometrium 1217 , and chorioamniotic membranes 1820 revealed that labor is a state of physiological inflammation; however, finding specific pathways implicated in preterm labor still remains an elusive goal. A possible explanation is that gestational tissues, and especially the placenta, are heterogeneous composites of multiple cell types, and elucidating perturbations in the maternal-fetal dialogue requires dissection of the transcriptional activity at the cell type level, which is not possible using bulk analyses.…”
Section: Main Textmentioning
confidence: 99%
“…The present study documents the molecular landscape of the NP and TP myometrium as well as the changes between these two stages. While previous genome-wide studies identify candidate mechanisms for the switch from nonlabor to labor states [40, 75, 76], results presented here report the way the myometrium reorganizes and adapts from nonpregnant to gravid preceding the switch for parturition. This is exemplified by the uniform increase of mRNA of parturition associated genes OXTR, GJA1, ZEB1 and PLCL1 during myometrial remodeling followed by the divergent change of expression patterns (Figure 1).…”
Section: Discussionmentioning
confidence: 79%